Transient Operation Strategies for MW-Scale SOC Systems. (10th July 2019) - Santhanam, Srikanth; Padinjarethil, Aiswarya; Tomberg, Marius; Heddrich, Marc P.; Ansar, Asif
Abstract : High temperature reversible Solid Oxide cell (rSOC) systems can operate efficiently in both fuel cell and electrolysis mode for energy storage and sector coupling. They are expected to attain MW and multi-MW capacities for industrial applications. Fast dynamic operation is required to interact with a renewable energy driven grid without storage. The challenges associated with fast dynamic operation must be addressed to realize its true market potential. The system should be able to achieve fast transition within a single operation mode and also switch between electrolysis and fuel cell peak operation in less than 30 minutes for a secondary or tertiary energy market. A control strategy to enable the expected fast dynamic operation is presented. It accounts for the thermal behavior of the reactor module and safeguards it against hot spots and out of specification temporal and spatial temperature gradients